La abstracción formal y la validación del razonamiento inductivo - Guzmán Vicente Burgoa, Lorenzo de ca. 21. Jh. (Sapientia, 2007)
It is commonly accepted that the justification of inductive reasoning remains a problem ever since Hume’s critique. Neither empiricism or logical positivism, on the one hand, nor rationalism and idealism, on the other, have succeeded in solving this problem. We believe that the answer could be found within the Aristotelian framework through a correct interpretation of the concept of formal abstraction which has been misunderstood or abandoned by many, even by Aristotelians from Antiquity and from more recent periods. The solution depends on noticing that a general conclusion derived from particular premises must be based on a previous process: the form’s (morphé) abstraction. If so, the conclusion is properly grounded in the premises and does not assert anything beyond justification, which is the classical difficulty in Aristotle’s epagogé.